A study of Some Electrical Properties of Te:S Thin Films Deposited at Angle Ó¨=70o - Khadum, Farah J.; Sabaa, Hanaa S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research a study of some electrical properties Of (Te) thin films with(S) impurities of(1.2%) were deposited at( Ó¨=700)by thermal evaporation technique .The thicknesses of deposited films were (1050 , 1225 , 1400 , 1575 nm) on a glass substrates of different dimensions . From X-ray diffraction spectrum, the films are polycrystalline .A study of (I-V) characteristic for thin films, the measurements of electrical conductivity (Ïƒ)and electrical resistance(R )vs. temperature( T) are done. Further a measurement of thermoelectric power, see beck coefficient and activation energies ( Ea, Es) were computed